FFB detector mobile apps assist in routes planning of FFB collection in oil palm / Saiful Shahrin Khamis - Khamis, Saiful Shahrin (Faculty of Plantation and Agrotechnology, 2019)
Oil palm industry is one of the major industry in Malaysia. There are many new technology and mechanization introduced for the oil palm industry. It is because to reduce the much dependent on manual labour to carry out the operations in the plantations. Harvesting and the evacuation of FFB is the most important operation in the plantations and must be done efficiently to maintain the quality and gain more profit to the company. The normal ways that use in the plantation to collect the FFB and loosen fruit by the collector is they need to stop at each palm through the harvesting path to find it before transfer to the platform and then send to the mill. The process will be difficult and take a time to evacuate the FFB. This study was done to design and develop the mobile applications that can assist in evacuation process. Android Studio Software was used to build the mobile applications that was targeted for the phone and tablet. The coding was take place to make the applications was functioned. This mobile applications can ease the process of evacuation FFB based on the coordinate get after harvesting process. Thus, it can give benefit for the evacuation FFB operation in the oil palm industry.